حجاجية اللّغة في السّور" الطّواسين" من القرآن الكريم - بلول, ايمان; بلول, ميس الريم; زوازية, وداد (جامعة الوادي - university of Eloued, 2023)
القرآن الكريم بدرجة أولى مازال يحتاج إلى الدراسة والتحليل والتدبر، فعلى الرغم من انكباب الباحثين على دراسته مند أنزل، مازال موضوع دراسة وتمعن، فهو لا يبلى على كثرة الدارسين له، لما فيه من معجزة وحكمة صالحة في كل زمان ومكان، فموضوعنا هو إبراز حجاجية اللغة من خلال ألفاظ التعليل والتراكيب الشرطية، وكذلك الأفعال الكلامية تبعا لتصنيف "سيرل" Searle"، في السور "الطاسين"، ومن هذا المنطلق نطرح الإشكال ما الجامع الحجاجي للسور الطواسين بدلالة خطاب لغتها؟. ركزنا في بحثنا هذا في جانبه النظري على مفهوم الحجاج تاريخه ونشأته مع التنويه إليه في الدرس العربي القديم والحديث، ويتبعها الوقوف بينا أسرار السور" الطواسين" والتعرف عليها وببيان فضلها. وفي الجانب التطبيقي بين فيه حجاجية اللغة في السور " الطواسين" من حيث ألفاظ التعليل (التعليل بالأسماء، التعليل بالحروف)، والتراكيب الشرطية (أدوات الشرط الجازمة، وغير الجازمة)، كما بينا بعدها حجاجية اللغة من حيث أفعال الكلام فكان لابدّ من تقديم تعريف للأفعال الكلام وتبنينا مقاييس سيرل وتصنيفه لها، مع وإبراز حجاجيتها في السور"الطواسين " من خلال توضيح الفعل الإنجازي فيها بالوقوف على الإخباريات، التوجيهات، الالتزاميات، التعبيريات والإعلانيات the Holy Qur’an in the first degree still needs study, analysis and contemplation, so although since its revelation everyone has studied it and we are still studying it and contemplating it, because of the miracle and wisdom that is valid in every time and place, our topic is to highlight the argumentativeness of the language through the words of reasoning and conditional structures, as well as Speech verbs according to the classification "Searle" in the Tawasin suras, and from this point of view, the forms are raised. In our research, we focused on the theoretical aspect of the concept of pilgrims, its history and origin, with reference to it in the ancient and modern Arabic lesson, followed by standing between the secrets of the Surah "Tawasin" and identifying it and explaining its virtue.In the applied aspect, the argumentativeness of the language was explained in the surahs "Al- Tawasin" in terms of the words of reasoning (the reasoning by names, the reasoning by letters), and the conditional structures (the assertive conditional tools, the non- assertive conditional tools). Speech verbs show Searle's metrics and his classification for them, highlighting their arguments in the "Tawasin" suras by clarifying the performing verb in them by standing on the indicative, directives, expressive commitments, and declaratives.
لسانيات عامة
Keywords: السور الطواسين، الحجة، النتيجة، التوجيه الحجاجي; the argument. The result. Argumentative directing. Tawasin suras